PERFORMANCE OF DAIRY COWS DURING DIFFERENT SEASONS WITH DAILY HERBAGE ALLOWANCE: A REVIEW - Listya Purnamasari; Josep Dela Cruz (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2022)
Pasture-based feeds are favored nowadays due to their cost-effectiveness and effect on animal welfare. Daily herbage allowance (DHA) affects the performance of dairy cows across different seasons. The key determinant of the performance of livestock is the dry matter intake (DMI) of herbage in pasture-based systems. A decline in average summer rainfall may result in considerably higher concentrate supplementation requirements to compensate for the loss in pasture growth and availability during autumn. Supplementation during autumn and winter boost total DMI and sustain milk output under grazing restrictions. Generally, milk production increases at high DHA but has no significant influence on milk fat content. In Spring, greater milk production lessens cows’ maintenance energy needs, and lower pasture content is linked to lower methane generation in the rumen. Methane generation declines in summer with increased digestibility at high intake levels. It is recommended to conduct an experiment exhibiting all seasons to eliminate factors that may affect the results across various studies. This review will understand variation in daily herbage intake of cows at pasture that allows the management of total intake to optimize milk production and identification of cows that are more efficient at converting feed into milk.